Stressing in the Fall: Effects of a Fall Break on Undergraduate Students - Poole, Heather; Khan, Ayesha; Agnew, Michael (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
Universities across Canada are responding to increasing levels of student stress and mental illness by introducing a fall break. However, scant research has investigated the effectiveness of this intervention. Our team assessed perceived stress and the number of stressors experienced by students at McMaster University using established self-report stress questionnaires, comparing stress before and after the break. We found that despite the widespread expectation that a fall break will decrease student stress, the effects of this intervention are not straightforward. Students experienced fewer stressors after the break than before it, but experienced higher levels of overall stress. Additionally, stress varied according to several demographic variables, revealing some groups to be at higher risk for stress-related problems. Given the wide-scale adoption of fall breaks, we hope that this investigation can initiate dialogue about the importance of evidence-based decisions in the development of stress-reduction interventions for Canadian university students.